A COMPARATIVE ANALYSIS OF RECOVERY METHODS ON LACTATE IN THE BLOOD AND HEART RATE AFTER TRAINING FOOTBALL PLAYERS - Junma, Montree (Journal of Sports Science and Health, 2023)
Purpose: The purpose of this research was to compare methods of physical recovery after training with static stretching, water stretching, ice massage, and applied Thai massage that had blood lactate and heart rate in football players. Methods: This research utilized a conditional counterbalanced design with 16 subjects, which were divided into 4 experimental groups and each group conducted 4 experiments times by alternating methods of physical recovery once a week. Included for a period of 4 weeks, then presented in the form of an accompanying table and essay, including finding the mean, standard deviation (S.D.), also analyzed repeated measures ANOVA with repeated measures and compared the differences in pairs by using Tukey's method. Results: Physical recovery was observed after training with static stretching (SS), ice massage (IM), applied Thai massage (MTM), and water stretching (WS). It was found that blood lactate concentration and heart rate decreased significantly at the .05 level. Comparing the concentration of lactate in the blood after physical recovery after training using different methods. The concentration of lactate in the blood after physical recovery with SW was different from SS, IM, and MTM with statistical significance at the .05 level. The average heart rate after recovery with SS was different from WS, IM, and MTM with statistical significance at the .05 level. Conclusion: Physical recovery after football player training through water stretching has more effectively reduced blood lactate concentration and heart rate than ice massage, applied Thai massage, and static stretching.